Responsibility for displacement: Between denial and obfuscation - Øverlid, Veronica (AUC Knowledge Fountain, 2016)
When refugees and migrants arrive in Europe, European states portray themselves as inadvertent hosts to unanticipated crises: well-intentioned, sorely-stretched, and attempting to negotiate a reasonable solution and find the middle ground between fairly balancing the needs of refugees and their own citizens. To the contrary, I argue that European states, like many other developed countries, themselves take part in creating conditions for displacement in the Third World. This is done through, among other things, international legal regimes for the global economy, trade, war, and the environmental. Although local factors also play an important role in Third World displacement, external interventions have a significant role to play and should be subject to equal scrutiny. For instance, climate change induced migration is attributable to the largest carbon emitters, and yet this group of states are unwilling to accept refugees from climate change. I argue that this mismatch between causation and responsibility is unsustainable and asylum policies aimed at containing refugees in the Third World through closed European borders, aid, and proposals for solely local solutions are highly misplaced. As European states continue to intervene deep into the economic, political and social sphere of Third World countries, they strip Third World states of their decision-making ability and impose policies in favour of affluent states, and uphold an international unequal system that lies at the core of displacement dynamics. Yet these dynamics are not reflected either in international refugee law or the other legal regimes governing war, economy, trade, or environment. This is because interventions are enabled through, among other things, international law itself; under the pretext of rectifying Third World problems. International law helps create a perception of the international as the saviour and the local as the problem. European and other developed states are able to obfuscate their roles in displacement and can deny responsibility for sheltering displaced people. Consequently, a global apartheid persists, where those who cause displacement maintain their vast privileges through international law, while most of the displaced that a just law should protect are left to suffer.